Mindfulness-based stress reduction : the MBSR program for enhancing health and vitality - Lehrhaupt, Linda Myoki (New World Library, 2017)
"The originator of the much studied - and much proven - eight-week Mindfulness-Based Stress Reduction (MBSR) course, Jon Kabat-Zinn, outlined a simple yet powerful approach to help anyone coping with the stress of a variety of psychological and physiological challenges. The authors, two of the leading MBSR teacher trainers in Europe, are ground readers in the practices that have been studied and proven effective. These include mindfulness meditation, walking meditation, eating meditation, Yoga, and Body-Scan. The authors provide step-by-step instructions, as well as illustrative real-life examples. Readers considering a course in MBSR will find information and inspiration while practitioners will gain a valuable tool for their teaching. Anyone experiencing or treating chronic challenges of mind, body, or spirit will find practical, motivational help here"--